REPAIRS TO HUNAT HATUN MOSQUE FROM THE OTTOMAN PERIOD TO THE PRESENT - Aksehirlioglu, Aysegul; Binan, Can Sakir (ILAHIYAT BILIMLERI ARASTIRMA VAKFI, 2021)
Monumental structures that achieve continuity through traces from the past to the present should be carefully preserved and handed down to future generations because of their social, cultural, religious, economic, and historical values and symbolic meanings. The monumental buildings of the Seljuk Period, which constitute a significant part of Turkey's rich cultural heritage, are important landmarks that deserve to be preserved for their strong sense of place and context, as determinants of urban perception and urban identity, and as memorials. Although Turkey has an abundant monumental architectural heritage, the issue of preserving these structures with their original values and ensuring their sustainability is not the main topic of conversation often enough. The buildings should be preserved as a whole, together with all the historical layers gained after the additions and repairs. In today's preservation criteria, the historical document quality of cultural assets is not limited to its original version but includes period annexes added later. Determining these additions, and transferring the monuments to the future with all their value, depend on proper maintenance and repair. The proper restoration process, which includes maintenance and repair, can be achieved by thoroughly understanding the repair chronology of the monument. The Hunat Hatun Complex in the center of the city of Kayseri is one of its most important structures, the determinant of its urban perception and identity. It is a collection of structures including a mosque, a madrasah, a tomb and a double bath located outside the city walls, east of Kayseri Citadel. Evliya Celebi mentioned the existence of an imaret building belonging to the complex, but there is no evidence of this structure today (Evliya Celebi, 2011). The Hunat Hatun Complex was built by Mahperi Hatun, the wife of Kayqubad I and mother of Giyaseddin Kaykhusraw II, during the most powerful period of the Seljuks (Akozan, 1969; Aslanapa, 1991; Eldem, 1982; Kuran, 1969; Sozen, 1970). The complex, about whose construction phase various opinions have been suggested, consists of a mosque, a tomb in the northeast corner of the mosque, a madrasah adjacent to the west of the north facade of the mosque, and, located diagonally in front of its west facade, a double bath that has almost completely lost its originality as a result of repairs. Hunat Hatun Complex is important because of its relationship with the city walls and citadel and especially because it represents the widespread design levels and construction techniques of the Seljuk architecture before the Mongolian sovereignty, exhibiting the conceptual approach of the period. It is a very significant architectural structure because it reflects the general characteristics of the period, such as iwan, crown gate, portico, cover systems, and facade design (Kuban, 2002). The mosque has a rectangular plan and a multi-legged mosque typology. The building is entered through two crown gates in the east and west that are rich in ornamentation. The most significant features of the mosque, distinguishing it from others, are the support towers/buttresses, round or rectangular in cross-section, located between and at the corners of thick perimeter walls. These architectural elements are considered to be connected to the location of the building. Because the building is opposite the Kayseri Citadel, it is thought that military architectural elements were used in the building with aesthetic concerns. The Hunat Hatun Complex has only survived to today because of the maintenance and repair work on it since it was built. The Prime Ministry Ottoman Archive, Kayseri Court Records, General Directorate of Foundations, Regional Preservation Board Archive and many written and visual resources were reviewed for the complex buildings to be examined in detail in this study. According to the data obtained as a result of the review, the complex, which is among the significant works of Seljuks and has existed for seven centuries, underwent extensive repairs between the classical and westernization periods of the Ottoman Empire. In the Republican period, preservation and restoration work was carried out on the building because it was considered a cultural heritage. In this article, according to the data obtained as a result of reviewing the resources for the complex, the restoration process of the building is examined chronologically, after a brief discussion of the preservation history of Turkey. First, the history and the architectural and structural features of the Hunat Hatun Complex are summarized. Then, the maintenance and repair work on Hunat Hatun Mosque from the Ottoman Period to the present is explained in detail. The original architectural features of the building are discussed, and the changes after repairs are noted. Then the changes to the building are evaluated in parallel with the developments in preservation in the evaluation section. The conclusion section interrogates the originality value of the building. In addition, conservation approaches that should be implemented for other similar cultural assets of Turkey are suggested. In this study, the restoration processes of Hunat Hatun Mosque, an important structure of Hunat Hatun Complex, which is the first complex in the Seljuk Period in Kayseri, are discussed based on different periods from the Ottoman period to the present. In this context, first, the construction, development and change, and architectural features of the Complex are briefly explained. To evaluate the preservation and repair process of the mosque, a detailed literature review was made, and based on the data obtained, the maintenance and repair works of the building were noted chronologically. The understanding of preservation in Turkey regarding the repair and restoration of monumental structures, as well as the preservation activities are discussed, and the effect of important developments in the field of preservation on the change and transformation of Hunat Hatun Mosque is determined. In the conclusion section, which can be considered research on the history of restoration, the originality value of the building after the preservation, restoration practices and interventions is questioned. This study discussing a conservation approach to be implemented for similar cultural assets is expected to be a guide for further studies.
Keywords: Turkish Islamic Arts; Seljuk architecture; Preservation; Hunat Hatun Mosque; Kayseri; Religion